Children of “Vulnerable Identity” Do They Have To Be Excluded? Some Reflections Based on Empirical Research - Ornacka, Katarzyna (Acta Universitatis Lodziensis. Folia Sociologica, 2014)
Childhood is a unique period of life, and it has a fundamental influence on human being’s process of development. Knowledge and experience gathered by a child has a great impact on his/her behaviour and relations with others. Identity(ies) of the child, especially its social aspect, is shaped through the acting process, in a specific social space. It is the key to understanding mechanisms taking place between an individual and society. Its form and shape are determined by a society as well as an individual depending on his/her position in the social structure. What are the commonalities and differences between the world of children of vulnerable identity and those who are brought up in “healthy” family systems? They form a separate social group and are present in various types of discourse. However, their social situation is different, much more difficult ‒ their life stories are complicated, and their firsthand experience is much bigger. What are their chances of being included in the mainstream? The purpose of the article is to find the answer to the question.